2013
DOI: 10.1111/ans.12371
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of rotational deformity: using a smartphone application is more accurate than conventional methods

Abstract: Measurement of a rotational deformity using a SP app was significantly more accurate and consistent than both VE and OT. We believe the currently available SP technology provides orthopaedic surgeons with a significantly better alternative method of determining the magnitude of rotational deformity when performing corrective osteotomies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 11 publications
3
21
0
Order By: Relevance
“…A systematic review of the literature [ 16 ] described all validated accelerometer-, magnetometer-, and photographic-based smartphone applications used as goniometers for peripheral joints and the spine. Researchers in Australia [ 17 ] more accurately measured the rotational deformity of a correction osteotomy using an application for iPhone. Peters et al [ 18 ] used an iPhone for acetabular cup placement in THA.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of the literature [ 16 ] described all validated accelerometer-, magnetometer-, and photographic-based smartphone applications used as goniometers for peripheral joints and the spine. Researchers in Australia [ 17 ] more accurately measured the rotational deformity of a correction osteotomy using an application for iPhone. Peters et al [ 18 ] used an iPhone for acetabular cup placement in THA.…”
Section: Introductionmentioning
confidence: 99%
“…indicated that this measurement method could generate an acceptable result. One study to measure the angle between two fixed Kirschner wires in four saw bone models demonstrated high accuracy and precision of smartphone measurement during rotational deformity assessment . Another study to assess its clinical suitability to correct the intraoperative femoral malrotation in patients with femoral nailing fixation demonstrated similar results …”
Section: Introductionmentioning
confidence: 95%
“…These techniques are user-dependent, and they are susceptible to inaccuracy and error. 2,[4][5][6][7] Over-correction and under-correction have been reported in the literature with error rates as high as 10%. 8 Furthermore, it is known that measured rotation at the time of surgery differs from post-operative radiographic measurements in up to 50% of cases.…”
Section: Introductionmentioning
confidence: 99%
“…8,10 Inclinometers and smart phone inclinometer applications have been recently used clinically in an attempt improve accuracy. 7 Traditionally, electronic inclinometers have been used by carpenters, surveyors, and engineers to assess tilt or slope. Electronic inclinometers have demonstrated accuracy in measuring static rotational differences as well as improving accuracy in total knee arthroplasty.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation